2015
DOI: 10.1109/temc.2014.2359239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Whole-Body Absorption Cross Section For Diffuse Exposure From Reverberation Chamber Measurements

Abstract: Abstract-An original experimental protocol is developed to assess the whole-body absorption cross section of objects with arbitrary shapes and materials in diffuse fields at any operating frequency. This approach is important for dosimetry specifically in realistic environments wherein diffuse fields can be prominent. For this application, the knowledge of the whole-body specific absorption rate is critical and can be determined from the human whole-body absorption cross section. The whole-body absorption cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Figure b shows an illustration of the setup for measurements in the RC. The working area of the chamber where fields have uniform distribution [Bamba et al, ] is indicated with dashed lines. Room dimensions are 5.7 × 4.1 × 2.8 m 3 (length × width × height) which provides a volume equal to 65 m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Figure b shows an illustration of the setup for measurements in the RC. The working area of the chamber where fields have uniform distribution [Bamba et al, ] is indicated with dashed lines. Room dimensions are 5.7 × 4.1 × 2.8 m 3 (length × width × height) which provides a volume equal to 65 m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of the ACS of a lossy object is required for many applications, including the characterization of lossy objects on electromagnetic wave propagation used for communications in multipath environments such as interiors of mass transit vehicles or aircraft loaded with cargoes or passengers [9], biometrics electromagnetic exposure studies such as human's specific absorption rate [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The averaged ACS can be measured in two ways. Firstly, it can be done by measuring the average net power transfer function G chamber [1], [11], [12], [13], or it can be determined by measuring the change of the reverberation chamber time constant τ [14].…”
Section: Introductionmentioning
confidence: 99%